Effects of fresnel corrections in the scattered field of general ellipsoids - Koay, J. Y.; Ewe, H. T.; Chuah, H. T. (2007)
The study of the scattered field of non-spherical scatterers is becoming an important field, especially in the remote sensing of vegetation. In this study, the scattered field of general ellipsoidal scatterers is formulated based on the generalized Rayleigh-Gans approximation, in which at least one of the dimensions of the ellipsoid is comparably smaller than the wavelength. The scattered field is formulated for the case in which far field approximations are used, as well as for the case in which the Fresnel zone effects are included. Results show that when the Fresnel corrections axe considered, the calculated backscattering cross section gives a better match with measurement data compared to when far field approximations are used.